Factors affecting the performance of the food and beverage companies in Indonesia - Fathaniyah Syahrami Putri; Nur Hijrah; Farah Margaretha Leon (Universitas Nusa Cendana, 2026)
This study evaluates the implementation of a mentoring program designed to enhance the competitiveness of Moms Nastar, a home-based pastry MSME in Banyuwangi Regency, Indonesia. Conducted as part of the Managerial Insight Development course in the Master of Management Program at the State University of Malang, the program addressed key business challenges, including limited product innovation, weak branding, the absence of business legality, underutilized digital marketing, inadequate human resource management, and the lack of financial record-keeping. Adopting a community-based intervention approach, the mentoring focused on five strategic areas: product innovation, business identity and legal registration, digital marketing optimization, human resource development, and basic financial management. The outcomes demonstrate notable improvements in product diversification, business branding, legal compliance, digital market presence, operational efficiency, and financial management practices. These enhancements contributed to increased business capacity and broader market reach, highlighting the effectiveness of integrated managerial assistance in supporting MSME development. The study contributes to the literature on entrepreneurship and MSME empowerment by demonstrating how structured mentoring can strengthen business sustainability and competitiveness through the application of practical management principles. Keywords: Capital Structure; Companies Performance; Cost Leadership; Food and Beverage Sector; Inventory Turnover; Liquidity; Sales Growth